2013
DOI: 10.3390/molecules180910973
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic and Inorganic Fertilizers Application on the Phytochemical and Antioxidant Activity of Kacip Fatimah (Labisia pumila Benth)

Abstract: Abstract:A study was conducted to compare secondary metabolites and antioxidant activity of Labisia pumila Benth (Kacip Fatimah) in response to two sources of fertilizer [i.e., organic (chicken dung; 10% N:10% P 2 O 5 :10% K 2 O) and inorganic fertilizer (NPK green; 15% N, 15% P 2 O 5 , 15% K 2 O)] under different N rates of 0, 90, 180 and 270 kg N/ha. The experiment was arranged in a randomized complete block design replicated three times. At the end of 15 weeks, it was observed that the application of organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
106
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 68 publications
11
106
3
4
Order By: Relevance
“…Though other researchers and co-workers showed that chicken dung 17 and sludge 18 can resemble soil conditioner and able to improve the nutrient supply in the soil for sunflowers, our finding showed the compost was not able to contributed towards TPC, DPPH and FRAP analysis. Our findings were also in contrast with 12 which showed the usage of fertilizer could enhance the production of secondary metabolites and improve antioxidant activity (DPPH and FRAP) of Labisia pumila herb. This may be due to different species of plants, fertilizer and the origin of the compost applied in the growth of plant.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Though other researchers and co-workers showed that chicken dung 17 and sludge 18 can resemble soil conditioner and able to improve the nutrient supply in the soil for sunflowers, our finding showed the compost was not able to contributed towards TPC, DPPH and FRAP analysis. Our findings were also in contrast with 12 which showed the usage of fertilizer could enhance the production of secondary metabolites and improve antioxidant activity (DPPH and FRAP) of Labisia pumila herb. This may be due to different species of plants, fertilizer and the origin of the compost applied in the growth of plant.…”
Section: Resultscontrasting
confidence: 99%
“…Whereas, fertilizer is used to support plant growth and yield. Application of organic manures along with chemical fertilizer was possible and reported by several researchers and co-workers 12,13 . While, application of EFB along with chemical, or organic or both chemical and organic fertilizer has not reported in tomato.…”
Section: Introductionmentioning
confidence: 99%
“…(Ibrahim et al, 2013). Furthermore, the use of organic manure increases soil fertility by improving its physical, chemical, and biological properties (Khalil et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Food and Agriculture Organization of the United Nations (FAO) developed a strategy named Integrated Plant Nutrition System (IPNS) to promote crop and soil productivity through the use of a balanced combination of chemical, organic and biofertilizers. Moreover, the consumers, nowadays, are greatly cocerned with the harmful effects of plant chemical fertilizers on their health, as well as polluting the environment [4]. The impact of different fertilizers on production of secondary metabolites in plants is not widely studied, yet some authors suggested that organic fertilization can enhance the production of these metabolites versus inorganic fertilizers [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the consumers, nowadays, are greatly cocerned with the harmful effects of plant chemical fertilizers on their health, as well as polluting the environment [4]. The impact of different fertilizers on production of secondary metabolites in plants is not widely studied, yet some authors suggested that organic fertilization can enhance the production of these metabolites versus inorganic fertilizers [4][5][6][7]. As no studies could be traced concerning the efficacy of various fertilizers on beet greens metabolites and in a continuation to our previous study regarding evaluation of the effect of different fertilizers on growth and bioconstituents of red beet bulbs [8], thus, the present work aimed at investigating the impact of fertilizers on some growth parameters, phytochemical constituents and biological activities of the beet leaves.…”
Section: Introductionmentioning
confidence: 99%